(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: Antibiotic prophylaxis is a common practice in children undergoing colostomy closure for anorectal malformation, Hirschsprung’s disease. Traditionally, antibiotics are given for unnecessarily longer period of time, which consumes scarce health resources having alternate efficient use. The present study was undertaken to compare the outcome between short-term and long-term antibiotic prophylaxis in colostomy closure. Materials & Methods: This randomized clinical trial was conducted in Dhaka Shishu Hospital, Dhaka over a period of 15 months from April 2001 to June 2002. Children admitted with anorectal malformation, Hirschsprung’s disease for colostomy closures were the study population. However, immuno-compromised children or children already getting antibiotics were excluded from the study. A total of 46 such children were consecutively included and were randomly allocated to long-term group (n = 21) and short-term group (n = 25). The long-term group received antibiotic up to 5th postoperative day, while the short-term group received the same antibiotic up to 2nd postoperative day. Transverse colostomy was the main procedure employed in colostomy closure; however, a few patients required sigmoid colostomy. The outcome measures were incidence of wound infection, hospital stay and cost of treatment. Result: Majority of the children were between 1 - 5 years of age (75% in short-term and 50% in long-term group) followed by under 1 year (10% in short-term and 40% in long-term group) and > 5 years (15% in short-term and 10% in long-term group). The overall male to female ratio was 3:1. Majority (85%) of the patients in both longterm and short-term groups belonged to lower income group. Over half (52.2%) of the children had anorectal malformations (ARM) and the rest (47.8%) had Hirschsprung’s disease (HD). Children were generally malnourished according to Gomez classification. Majority (91%) was operated on by transverse colostomy and few (9%) by sigmoid colostomy. Three patients in each group developed postoperative wound infection. Blood culture of none of these patients yielded growth of any organism, though wound swab culture did so in 5 cases out of 6 infected patients. In 2 cases, the organism was E.coli, in 2 cases, it was Pseudomonas and in one case Staph. aureus. Total cost of antibiotics in short-term therapy was less than 50% of that required in long-term therapy. The outcome in terms of recovery, complications and postoperative hospital stay was no different between groups. Conclusion: The study concluded that short-term antibiotic prophylaxis is as efficacious as long-term in preventing wound infection in patients with colostomy closure for anorectal malformation and Hirschsprung’s disease. Short-term antibiotic prophylaxis is cost-effective Ibrahim Cardiac Med J 2014; 4(2): 43-48